Técnicas en corte y confeccón de faldas y su incidencia en el proceso enseñanza aprendizaje a Estudiantes del Gremio de Maestras Modistas del Guayas Cantón, Guayaquil. - Garrido León, María Marlene (2018)
This research work entitled techniques in tailoring of skirts and their impact on the process teaching learning students from the Guild of teachers dressmakers of the Guayas, Guayaquil Canton realized it on the basis of a need and the purpose of obtain an expressive learning that helps the students to a better understanding of the techniques in making of skirts, the teaching and learning is the process that relates to the teacher and student to carry a given context and activities that transmit the teachers to facilitate better learning and achieve the goals, and so the students can perform their own knowledge using all existing resources. In this paper the method that was used was the inductive, in order to observe the different techniques and achieve the results that allow the possibility of the argumentation that gets to understand the scope of the training in the teaching and learning in skirts dressmaking techniques. Descriptive because the survey technique applied to know the flaws and strengths of the specialty, and field because it will be executed in the place where the problem lies. This material is designed with techniques and methods for its implementation in order to strengthen the knowledge of the students.